EFFECT OF TUBE PASS RATIOS AND FLOW PASS CONFIGURATIONS ON THE THERMAL AND HYDRAULIC PERFORMANCE OF THE ALUMINIUM MINI-CHANNEL HEAT EXCHANGER - THOO, KOK KEONG (2013)
Aluminium mini-channel heat exchanger or in short MCHX is gaining much popularity in the field of HVAC&R. MCHX is a suitable choice to replace conventional fin-tube condensers due to its high heat transfer area per unit volume, lightweight and resistance to galvanic corrosion. Dueto the high energy consumption of air conditioners, it has become almost mandatory for design engineers to come out with energy efficient equipment. In view ofthis, a research work has been carried out to determine the effectof different flow pass configurations and tube pass ratios to the thermal and hydraulic performance of MCHX and to come out with an optimum MCHX design. A numerical simulation using known correlations for condensing coefficient and pressure drop on the refrigerant side was carried out.